USE OF AUTHENTIC MATERIALS IN TEACHING LISTENING. ("Conference on Universal Science Research 2023", 2023)
Any imagination when it comes to pedagogical creativity it is necessary to be able to distinguish constructed projects from real creativity. Because in practice that untested imaginary ideas sometimes cause great damage to pedagogical work. Pedagogical personnel in accordance with the requirements of the development of the educational system high professional training and ideological-political maturity, general issues of continuous growth of the level of culture are raised. The peoples of our country in educating their students ideologically and politically using important events, holidays and memorable dates in his life is important.